Analisis Pengaruh Investment Opportunity Set, Profitabilitas, dan Dampaknya terhadap Dividend Payout Ratio: Studi pada Perusahaan LQ45 di Indonesia - Muhammad Alfa Niam (Owner : Riset dan Jurnal Akuntansi, 2025)
The purpose of this study is to investigate the effect of investment opportunity set (IOS) and profitability level (ROA) on dividend payout ratio (DPR) in companies listed on the Indonesia Stock Exchange and indexed in LQ45 from 2018 to 2021. This study fills the gap in previous research that showed inconsistent results regarding the influence of IOS on dividend policy in emerging markets. Using purposive sampling technique, 19 entities were selected as samples. Multiple regression analysis using SPSS 21 was employed as the analytical approach. The findings of this study indicate that IOS does not affect the Dividend Payout Ratio. Meanwhile, profitability (ROA) has a positive and significant effect on the Dividend Payout Ratio. This indicates that in the Indonesian context, where pyramid ownership structures are common, shareholders have more control over the company. Additionally, companies that can manage their assets effectively and efficiently create strong finances. This achievement is obtained by generating sufficient profits, so that companies are believed to be able to distribute part of their profits to shareholders in the form of dividends. The likelihood of a company distributing dividends increases if it achieves potential profits.